GOOGLE CLASSROOM ON STUDENT WRITING ASSESSMENT (case study on students’ perception) - Mariyatul Kiptiyah; Untung Untung; Ana Yuliati; Rosa Sonia (Universitas Madura, 2024)
Writing serves as a reflective practice. Beside, Writing acts as a self-assessment tool, enabling students to evaluate their own language performance and progress. This constructive feedback loop not only fosters a deeper understanding of language nuances but also motivates students to actively work towards refining their writing skills. In essence, writing becomes a dynamic and introspective exercise that contributes significantly to the continuous development of students' language abilities. Google Classroom as an alternative facilitates to motivate students write. Students can write and do assignments through digital/online applications (Google classroom) such as documents, presentations and educational videos, and share student learning experiences. Google Classroom introduces an innovative resolution for educators by simplifying the monitoring of online assignments. This platform provides a transformative solution, streamlining the process for teachers. Through this tool, educators can efficiently oversee and track students' assignments in the digital realm. It revolutionizes traditional teaching methods by offering a seamless interface that enhances the overall experience of managing assignments. This technological advancement empowers teachers to monitor progress in real-time, allowing for more personalized instruction and timely feedback